The Principle of Equal Rights of Churches and Other Religious Organizations - Mirosław Sitarz (Kościół i Prawo, 2015)
The principle of equal rights of churches and other religious organizations is a principle of Catholicism. It can be read from the principle of the pluralistic society contained in the model of the relations between Church and State developed by the Second Vatican Council. Under Polish law it is regulated in Article 9(2/3) of 17 May 1983 Act on the Guarantees of the Freedom of Conscience and Faith and in Article 25(1) of the 2 April 1997 Constitution of the Republic of Poland. In the axiological and legal basis of the principle of equality of churches and other religious organizations we can also include equal rights and dignity and freedom of conscience and religion.